O desenho como expressão e representação nos processos criativos em design - Carmo, Marcelo Kammer Faria do (2018)
This research investigates the creative means used by the product designer to express his or her design project. In the field of design, design and creativity are inherent in the activity of the designer and together constitute the raw material of innovation. Drawing allows the visualization of ideas, facilitating the organization and the task of communicating the thought in the course of the creative process. We interviewed ten experienced product designers working in the city of São Paulo, in their working environment. Their work experience is at least 15 years. In order to study the designer’s creative process and his or her relations with the market, we rely on the systemic model of creativity proposed by Csikzentmihalyi who considers appropriate to study design as an applied social science, since it emphasizes the creativity related to external as well as internal factors. Creativity results from the integration of the subject -- the designer -- in a domain -- the design -- defined in a field of action in a society. The analysis of the interviewees’ reports, the observation of the materials used the relationships with clients and work partners allowed a better understanding of the design and its relations with the creative processes in design. We concluded that drawing manifests itself in various forms and expands with actions that go far beyond the drawing on paper, such as three-dimensional elaborations, collages, photographic records, use of forms and materials found at random, they all can serve to communicate and make feasible concretization of what the designer imagined. The popularization of the computational technologies or IT has been operating modifications in culture, as well as in design, and it can be seen in many stages of the project. Finally, we came to the conclusion that the creative processes in design value the design in an expanded concept, extended to the use of different materials, that take into account improvisation. The first forms that appear in the creative process absorbs the changes made into computers, thus constituting a new way of drawing.